Menstrual cycle phase has no influence on performance-determining variables in endurance-trained athletes: The FENDURA project - Taylor, M. Y.; Osborne, J. O.; De Martin Topranin, V.; Engseth, T. P.; Solli, G. S.; Valsdottir, D.; Andersson, E.; Øistuen, G. F.; Flatby, I.; Welde, B.; Morseth, B.; Haugen, T.; et al. (Medicine & Science in Sports & Exercise, 2024)
Female athletes frequently perceive performance changes throughout the menstrual cycle (MC). However, if and how the MC influences performance-determining variables remains unclear.